Studies on laser design and laser micro-machining - Chen, Yihong. (2008)
Since the first laser was operated in 1960, extensive research and development have been undertaken leading to a rapid growth in both laser technology and laser applications. With its increasing use in material processing, the need for further study and improvement of the laser beam performance becomes necessary to achieve optimal processing quality. The first objective of this project, therefore, was to investigate the thermal lensing phenomenon of a laser medium which has the most significant effects on the laser beam of a solid state laser. Laser beam quality characterisation, calculation and measurement of thermal lensing characteristics, study of the stability of a thermal lensing resonator, and the study of the efficiency of pumping cavities constitute the essential part of this project. The second objective of this project was to investigate the use of solid-state lasers for micro-machining of materials. As examples, two typical applications, laser micro-engraving of photomasks and laser micro-drilling of various engineering materials, are studied in the project and presented in this thesis.